A comparative study of the marketing strategies of existing seafoods restaurants in Miagao, Iloilo - Cabello, Mary Ann; Escalante, Doreen; Gapulan, Evan John; Marasigan, Hazel; Umacob, Iris Ann
Executive summary-The ultimate goal of this study is to identify the marketing strategies that seafoods restaurants in Miag-ao, Iloilo apply. The findings are utilized to analyze the relationship of marketing strategy and business profitability by comparing the performances of the six seafood restaurants. The results of the study, based on the interviews conducted with the management of every restaurant, revealed several facts : (1) size and accessibility affects number of visitors ; (2) the promotion strategy dominates marketing mix components ; (3) food differentiation attracts customers ; (4) knowledge of marketing strategy increases business profitability, leads to aggressive expansion plans. These are only some of the findings, the rest is explained in the corresponding sections of the discussions. Based on the findings, the researchers outlined several recommendations or suggestions of improvement for existing the restaurants, and tips for interested investors in the seafoods business of Miag-ao, Iloilo. Among others these include (1) the accessibility of the location, which means the provision of transportation for customers ; (2) pursue aggressive promotions campaign to boost the image of the business against competitors ; (3) make available a wide array of food choices ; (4) employ professional help for designing marketing strategies.